2019
DOI: 10.1101/722595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon dots for efficient siRNA delivery and gene silencing in plants

Abstract: The Initiation of RNA interference (RNAi) by topically applied double stranded RNA (dsRNA) has potential applications for plant functional genomics, crop improvement and crop protection. The primary obstacle for the development of this technology is efficient delivery of RNAi effectors. The plant cell wall is a particularly challenging barrier to the delivery of macromolecules. Many of the transfection agents that are commonly used with animal cells produce nanocomplexes that are significantly larger than the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…siRNA applied with a nuclease inhibitor or polybrene which binds dsRNA was still detectable at 24 h. Both sets of experimental results strongly suggest that nucleases act as a barrier to efficient dsRNA delivery. This assertion is further supported by recent publications demonstrating that agents such as carbon dots, single-walled carbon nanotubes, and clay nanosheets enhance nuclease stability and delivery efficiency of applied nucleic acids in plants (Mitter et al, 2017;Demirer et al, 2019;Schwartz et al, 2019).…”
Section: Nuclease Stability As a Barriermentioning
confidence: 56%
See 2 more Smart Citations
“…siRNA applied with a nuclease inhibitor or polybrene which binds dsRNA was still detectable at 24 h. Both sets of experimental results strongly suggest that nucleases act as a barrier to efficient dsRNA delivery. This assertion is further supported by recent publications demonstrating that agents such as carbon dots, single-walled carbon nanotubes, and clay nanosheets enhance nuclease stability and delivery efficiency of applied nucleic acids in plants (Mitter et al, 2017;Demirer et al, 2019;Schwartz et al, 2019).…”
Section: Nuclease Stability As a Barriermentioning
confidence: 56%
“…The applied siRNA was extracted from the samples and analyzed by anionic exchange HPLC. Results indicate that siRNA applied without a nuclease inhibitor or polybrene was completely degraded by 6 h. siRNA applied with nuclease inhibitors or polybrene was still detectable at 24 h. efficiency in plant cells (Bennett et al, 2017;Demirer et al, 2019;Schwartz et al, 2019).…”
Section: Cellular Uptake As a Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Different classes of adjuvants, including cationic nanoparticles, surfactants, clay nanosheets, peptide-based agents, and carbon dots have been used to boast plant defense against pests by facilitating the delivery of exogenous dsRNAs through the cell wall and subsequently cell membrane (Jiang et al, 2014;Mitter et al, 2017a;Schwartz et al, 2019;Worrall et al, 2019;Zheng et al, 2019). Indeed, it has been shown that these adjuvants improved plant defense against virus infection by increasing the uptake of dsRNA into plant cells and by protecting the dsRNAs from early degradation (Unnamalai et al, 2004;Mitter et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this formulation also seems to facilitate uptake and systemic dissemination within the sprayed host plant [67]. The use of a class of very small nanoparticles, called carbon dots, for the delivery of siRNA to the Nicotiana benthamiana and tomato plants, has also been reported [87]. In addition, liposome-based delivery method has been applied in insects, fungi, and nematodes [88,89,90] with success in altering gene expression and/or mortality.…”
Section: Formulation Of Dsrna/sirnamentioning
confidence: 99%